Isolated reefs support stable fish communities with high abundances of regionally fished species. Issue 9 (16th March 2021) - Birt, Matthew J.; Cure, Katherine; Wilson, Shaun; Newman, Stephen J.; Harvey, Euan S.; Meekan, Mark; Speed, Conrad; Heyward, Andrew; Goetze, Jordan; Gilmour, James
Abstract: Anthropogenic impacts at isolated and inaccessible reefs are often minimal, offering rare opportunities to observe fish assemblages in a relatively undisturbed state. The remote Rowley Shoals are regarded as one of the healthiest reef systems in the Indian Ocean with demonstrated resilience to natural disturbance, no permanent human population nearby, low visitation rates, and large protected areas where fishing prohibitions are enforced. We used baited remote underwater video systems (BRUVS) to quantify fish assemblages and the relative abundance of regionally fished species within the lagoon, on the slope and in the mesophotic habitat at the Rowley Shoals at three times spanning 14 years and compared abundances of regionally fished species and the length distributions of predatory species to other isolated reefs in the northeast Indian Ocean. Fish assemblage composition and the relative abundance of regionally fished species were remarkably stable through time. We recorded high abundances of regionally fished species relative to other isolated reefs, including globally threatened humphead Maori wrasse ( Cheilinus undulatu s) and bumphead parrotfish ( Bolbometopon muricatum ). Length distributions of fish differed among habitats at the Rowley Shoals, suggesting differences in ontogenetic shifts among species. The Cocos (Keeling) Islands typically had larger‐bodied predatory species than at the Rowley Shoals. Differences in geomorphology, lagoonal habitats, and fishing history likely contribute to the differences among remote reefs. Rowley Shoals is a rare example of a reef system demonstrating ecological stability in reef fish assemblages during a time of unprecedented degradation of coral reefs. Abstract : Fish assemblage composition and the relative abundance of regionally fished species were remarkably stable through time at the Rowley Shoals. We recorded high abundances of regionally fished species relative to other isolated reefs, including globally threatened humphead Maori wrasse ( Cheilinus undulatus ) and bumphead parrotfish ( Bolbometopon muricatum ).